Serum bone Gla protein and carboxyterminal cross-linked telopeptide of type I collagen in patients with Cushing's syndrome. Issue 849 (July 1996) - Sartorio, A.; Conti, A.; Ferrario, S.; Passini, E.; Re, T.; Ambrosi, B.
Abstract : Serum bone Gla protein, a marker of bone formation, and carboxyterminal cross-linked telopeptide of type I collagen levels, an index of bone resorption, were evaluated in eight patients with active Cushing's syndrome and in four with 'preclinical' Cushing's syndrome, before and after surgery. In basal conditions, serum bone Gla protein levels were significantly lower (p < 0.0001) in patients with active Cushing's syndrome (1.0 +/- 0.35 ng/ml) than in controls (5.4 +/- 0.15 ng/ml); two out of four patients with the 'preclinical' form had reduced bone Gla protein levels, while in the other two cases levels were in the normal range. Serum levels of carboxyterminal cross-linked telopeptide of type I collagen (3.0 +/- 0.4 ng/ml), although slightly reduced, were similar to those recorded in controls (4.1 +/- 0.3 ng ml), both in patients with active and with preclinical Cushing's syndrome. After surgery serum levels of both marker proteins significantly increased in seven out of eight patients with active Cushing's syndrome; in one patient, who was not cured after surgery, bone Gla proteins levels remained lower than in normals, while levels of carboxyterminal cross-linked telopeptide of type I collagen had a transient increase after six months. In the two patients with a 'preclinical' Cushing's syndrome who underwent surgery, a significant rise of the levels of both marker proteins was observed, similar to that observed in patients with active Cushing's syndrome. It was concluded that serial determinations of these new markers of bone formation and resorption may be usefully employed to follow-up the clinical course of Cushing's syndrome and provide information on the rate of bone turnover in response to medical and/or surgical therapies. Moreover, the evaluation of these markers in preclinical states of Cushing's syndrome might suggest the need for surgery.